Debate about Pensions — Reply and Response - Martin Werding; Ernst Niemeier (Wirtschaftsdienst)
Abstract In its June 2020 issue, Wirtschaftsdienst published an article entitled „Beitragsfinanzierung im ‚demografiegestressten‘ Rentensystem möglich“ by Ernst Niemeier. Martin Werding takes a different view in a reply, and Ernst Niemeier explains his point of view in a response.